PENYULUHAN DAN PELATIHAN INOVASI PRODUK PENGERAJIN BAMBU TUSUK SATE DAN DIKEMBANGKAN MENJADI KERAJINAN BESEK (Di Lingkungan Dusun Dadapan Desa Tinalan Kota Kediri) - Tripariyanto, Afiff Yudha; Indrasari, Lolyka Dewi; Komari, Ana; Rahayuningsih, Sri; Safi'i, Imam; Widodo, Silvi Rushanti (Jurnal Abdi Masyarakat, 2020)
ABSTRACT Indonesia is one country that is overgrown with bamboo plants in large quantities, both interms of quantity and type. This plant has long been used for many purposes, ranging frommaking household appliances to furniture. But sometimes, in the community bamboo handicraftproducts tend to be still less prestigious than other raw materials such as wood. In fact, throughinnovation and a unique processing, this product can be in demand not only in the local market,but also in foreign markets. Awareness of the world community to use environmentally friendlyproducts helped boost the demand for bamboo commodities. This also makes the prospect of thebamboo industry getting better, especially for foreign markets. This Community Service activityoccurred because of the development of the use of bamboo so much that an idea emerged to takethis title. Community service is divided into three channels, namely: 1. Provision of initialmaterial about bamboo material innovation and questions and answers. 2. The practice of makingwoven baskets.3. Hold the finishing of the craftsman. By joining the community serviceactivities, the skewers craftsmen get a lot of knowledge, developments and innovations ofbamboo material at this time that can be used as a provision for new businesses to increase thesale value and economy so that the income of the craftsmen can also increase. Keywords: Product Innovation, Bamboo, Crafts, Wicker.ABSTRAKIndonesia merupakan salah satu negara yang ditumbuhi tanaman bambu dalam jumlahyang banyak, baik dari segi jumlah maupun jenisnya. Tanaman ini sudah sejak lamadimanfaatkan untuk banyak keperluan, mulai dari membuat perkakas rumah tangga hinggamebel. Namun terkadang, di masyarakat produk kerajinan bambu cenderung masih kalah pamordibanding bahan baku lain seperti kayu. Padahal, lewat inovasi serta proses pengolahan yangunik, produk ini bisa diminati tidak hanya di pasar lokal, tetapi juga pasar mancanegara.Kesadaran masyarakat dunia untuk menggunakan produk ramah lingkungan ikut mendongkrakpermintaan komoditas bambu. Ini juga yang membuat prospek industri bambu kian baik,khususnya untuk pasar luar negeri. Kegiatan Pengabdian Masyarakat ini terjadi karena adanyaperkembangan penggunaan bamboo yang sangat banyak sekali sehingga munculah ide utukmengambil judul ini. Pengabdian masyarakat ini terbagi dari tiga alur yaitu : 1. Pemberian materiawal tentang inovasi material bamboo dan Tanya jawab. 2. Praktek pembuatan anyaman besek.3.tahapan Finishing hasil pengrajin. Dengan mengikuti kegiatan pengabdian masyarakat tersebutpara pengrajin tusuk sate mendapatkan banyak sekali pengetahuan,perkembangan dan inovasiinovasi material bamboo saat ini yang bisa digunakan sebagai bekal usaha baru untukmeningkatkan nilai jual dan ekonomi sehingga pendapatan para pengrajin juga bisa bertambah. Kata Kunci : Inovasi Produk,Bambu,Kerajinan,Anyaman.